Terms and Conditions Applicability Muamalat - Rahmat; Asmuni; Tuti Anggraini; Ade Khadijatul Z. Hrp (PT Inovasi Pratama Internasional, 2023)
Aspect this elaborate agreement with the free, prohibition of usury and avoidance gharar, avoidance qimar and maisir, as well as suitability contract with maqashid sharia All studies This concludes that arrangement contracts are very important for efficacy, Muamalat, and ensuring obedience to internal sharia principles in transaction finance. Method This collects data through related literature, with agreement from Muamalat, like books, journals, and scientific articles. Research results this is a) Consent with the free method agreement That made for fulfillment the will of the parties in agreement, and it is compatibility between them to fulfill obligations with those shown with imitation, writing, moving hand, or act. b) Prohibition of usury and avoidance gharar is a prohibition to protect treasure from loss and the loss of enmity arising in people from this type of sale. c) Avoidance Qimar and Maisir is a game that has gains and losses for perpetrators of crime. d) A compatibility contract with Maqashid Syari'ah is a contract. No one can be opposed to the general public's interest.